Efektivitas Pemberian Aroma Terapi Lemon Terhadap Penurunan Tingkat Kecemasan Pada Ibu Nifas - LM. Zainal Abidin K; Altahira, Sutrisna; Sapril (Jurnal Sains & Kesehatan, 2025)
Postpartum anxiety can have a negative effect on the baby, the mental state of the mother of the baby herself, and her marital relationship. Lemon aromatherapy is one way to overcome anxiety such as anxiety experienced by pregnant and postpartum mothers. The purpose of this study was to determine the effectiveness of giving lemon aromatherapy to reduce anxiety levels in postpartum mothers. This type of research is a pre-experimental experimental study with a one-group pretest-posttest design. The population in this study was 30, namely all postpartum mothers at the Wakambangura Health Center in 2023. The sample in this study was the entire population used as a sample, namely 28 postpartum mothers at the Wakambangura Health Center in the period February - March 2023. Data collection was carried out during February-March 2023 using the interview method using a questionnaire instrument. Data were analyzed univariately and bivariately with the Chi-Square test. The results of the bivariate analysis showed an influence variable with a value (p-value = 0.002). Conclusion: Giving Lemon Aromatherapy to postpartum mothers is effective in reducing anxiety levels at the Wakamangura Health Center, Central Buton Regency.